Robot Age: Considering Robot Origin and Voice Accent - Barfield, Jessica K. (Proceedings of the AAAI Symposium Series, 2024)
This paper investigates how social cues may influence judgements of a robots perceived age. To investigate this topic a 3 x 3 factorial study was run with the Misty II robot presenting with American, Chinese, and Mexican national origins and voice accents. In the study, the participant’s task was to estimate the robots’ age as a function of the robot’s origin and spoken accent. The results showed that Misty was thought to be the age of a teenager, but that females judged Misty to be significantly older than males. However, versions of Misty which presented with an American accent tended to produce more agreement among males and females in estimates of robot age than robots presenting with an accent identifying a Chinese or Mexican identity. Implications for the design of robot support systems for the elderly is discussed.